A Verification-Centric Software Development Process for Java - Zimmerman, D.M.; Kiniry, J.R. (2009 Ninth International Conference on Quality Software, 2009)
Design by contract (DBC) is an oft-cited, but rarely followed, programming practice that focuses on writing formal specifications first, and writing code that fulfills those specifications second. The development of static analysis tools over the past several years has made it possible to fully embrace DBC in Java systems by writing, type checking, and consistency checking rich behavioral specifications for Java before writing any code. This paper discusses a DBC-based, verification-centric software development process for Java that integrates the Business Object Notation (BON), the Java Modeling Language, and several associated tools including the BON compiler BONc, the ESC/Java2 static checker, a runtime assertion checker, and a specification-based unit test generator. This verification-centric process, reinforced by its rich open source tool support, is one of the most advanced, concrete, open, practical, and usable processes available today for rigorously designing and developing software systems.